Determinants of Firm Value: Evidence from Corporate Governance, Sales Growth, Firm Age, and Tax Planning - Anak Agung Diah Kencana Dewi; Ni Luh Gde Novitasari; Ni Luh Putu Widhiastuti (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: A company’s value reflects management’s success in running the company; an increase in a company’s value indicates that the company has effective management and is capable of consistently generating profits in the future. This study aims to test and obtain empirical evidence of the influence of independent commissioners, audit committees, sales growth, firm age, and tax planning on firm value in companies in the textile and apparel subsector listed on the Indonesia Stock Exchange from 2022 to 2024. Method: The population in this study consists of 19 companies in the textile and apparel subsector listed on the Indonesia Stock Exchange from 2022 to 2024. Sampling was conducted using purposive sampling, resulting in 17 companies with three years of data, yielding a total of 51 research samples. The data were analyzed using multiple linear regression. Findings: The audit committee and sales growth have a positive impact on firm value. This means that the presence of an audit committee can increase investor confidence, thus increasing firm value. Similarly, increased sales growth indicates increased revenue, thus increasing firm value. Meanwhile, independent directors, firm age, and tax planning have no impact on firm value, indicating that these factors do not contribute to enhancing or diminishing a company's overall market valuation. Implications: The findings suggest that companies should strengthen the effectiveness of audit committees and focus on increasing sales growth to enhance firm value. For investors, these results indicate that audit committee performance and sales growth are important considerations in evaluating firm value.